PENGARUH MOTIVASI INTRINSIK, KNOWLEDGE MANAGEMENT, DAN KOMITMEN AFEKTIF DALAM MENINGKATKAN KINERJA SDM (Study Kasus Pada Dinas Pertambangan Dan Energi Kab. Kolaka Timur) - Candra Jamir; Wasitowati Wasitowati (Jurnal Ekonomi dan Bisnis, 2016)
ABSTRACTResearch problems that occur in the Office of Mining and Energy Kolaka East that is notachieving the performance of human resources to the maximum, which some realization ofthe activities of the program that had been planned was not realized in 2013 and 2014, therate of employee absenteeism average of 10 each month, employees who excel not given aspecial award for instance certificate exemplary employee, some employees are less eagerto work is weak science related to the work done and the ability to understand the technologyrelated to the job in question and kuarang initiative in carrying out the work, less industriousand less responsible is custom-tow nuda jobs such as typing letters, pengagendaan lettersand documents. Some factors that affect the performance of the Office of Human ResourcesDepartment of Mines and Energy East Kolaka are: (1) Intrinsic Motivation, (2) KnowledgeMangement, (3) and Affective Commitment. Samples from this study are employees of theDepartment of Mines and Energy East Kolaka totaling 46 respondents. Data collected bydistributing questionnaires to the respondents and then the data were analyzed by usingtest reliability and validity of some linear regression. Results of the study showed that partial,Intrinsic Motivation, Knowledge Management and Commitment Affective together positive andsignificant impact on the performance of human resources. This is indicated by SimultaneousTest results that show significant F value of 0.000 is smaller than α = 0.05. In the partial testresults indicate for the variable Intrinsic Motivation (X1) has a significance value of 0.001 t,variable Knowledge Managment (X2) has a significance value of 0.041 t, and for AffectiveCommitment variable (Y1) has a significance value of 0.000 t. Intrinsic Motivation, KnowledgeManagement and Commitment Affective able to contribute to variable HR performance of 0.916or 91.6% while the remaining 8.4% is the contribution of other variables not included in thisstudy.Keywords : Intrinsic Motivation, Knowledge Management, Affective Commitment, Performanceand Human Resources, the Department of Mines and Energy East Kolaka.